AB0260 Comparison of rheumatoid arthritis (RA) patient parameters at anti-TNF treatment initiation demonstrates wide variability over time in a large real-life cohort treated with infliximab. (23rd January 2014) - Chow, A.; Thorne, C.; Bensen, W.; Choquette, D.; Rampakakis, E.; Sampalis, J.; Otawa, S.; Khalil, S.
Abstract : Objectives: Anti-tumor necrosis factor alpha (anti-TNFα) agents revolutionized RA treatment by significantly reducing joint pain and inflammation, inhibiting disease progression, and improving patient function and quality of life(1). However, anti-TNFα agents are more expensive than traditional disease-modifying antirheumatic drugs (DMARDs) which may limit patient access. Methods: Data were obtained from an ongoing, Canadian registry of patients initiating Infliximab as first biologic or after being treated with a biologic for less than six months. Patients who had at least one follow-up visit at 6 months were included in this analysis. Based on their enrolment year, patients were divided in three groups (2002-2005, 2005-2008, and 2008-2011). Results: A total of 628 patients were included in this analysis, among whom 288 (45.9%), 217 (34.6%) and 123 (19.6%) were enrolled in 2002-05, 2005-08, and 2008-11, respectively. A trend towards earlier initiation of Infliximab was observed with the mean (SD) disease duration at baseline decreasing from 11.2 (10.3) years in 2002-05 to 9.2 (9.6) in 2005-08 and 9.6 (9.8) in 2008-2011 (P=0.072). In agreement, fewer patients were treated with ≥4 (25.7% vs. 12.1% vs. 3.3%, respectively) DMARDs prior to Infliximab initiation (P<0.001). Patients in more recent years had significantly lower DAS28 (5.9 vs. 5.4 vs. 4.3; P<0.001), swollen joint count (13.4 vs. 9.8 vs. 5.6; P<0.001), tender joint count (15.4 vs. 12.0 vs. 6.3; P<0.001), ESR (35.7 vs. 31.4 vs. 26.0 mm/h; P<0.001), and CRP (22.7 vs. 18.7 vs. 13.3 mg/L; P=0.006) at baseline. Interestingly, a shift from public to private insurance coverage (37.8% vs. 44.0% vs. 55.7%; P=0.007) and an increase in the proportion of patients employed (29.6% vs. 38.2% vs. 44.2%; P=0.011) was observed in more recent years. Furthermore, unemployment due to disability also decreased over time (40.6% vs. 32.3% vs. 26.9%; P=0.080). However, employment rate was maintained stable even after 24 months of treatment with Infliximab, regardless of enrolment period. After 12 months of treatment, a significantly higher proportion of patients enrolled more recently achieved DAS28 (21.4% vs. 38.9% vs. 44.8%; P=0.001), SDAI (9.3% vs. 21.7% vs. 17.2%; P=0.024) and CDAI (9.3% vs. 19.5% vs. 17.8%; P=0.023) remission. Conclusions: In this long-term, real-world Canadian registry, Infliximab was initiated earlier in the disease course in more recent years. This was associated with lower disease activity at baseline, as well as with increased remission rates, reduced unemployment due to disability and a shift from public to private payer coverage. References: Singh JA et al. Cochrane Database Syst Rev 2009; 4: CD007848 Disclosure of Interest: None Declared